The Representation of Muslims in Rudyard Kiplingâs Short Stories: A Postcolonial Perspective - Mugijatna, M. (Al-Jamiah Research Centre, 2014)
This article studies Rudyard Kiplingâs four short stories, âWee Willie Winkieâ, âThe Recrudescence of Imrayâ, âThe Story of Muhammad Dinâ, and âWithout Benefit of Clergyâ. The purposes of this research are to describe the representation of Muslims in the four short stories and to describe how the representation of Muslims in the four short stories represents British colonization in India. In this paper, I employs textual study methodology using narrative analysis, binary-opposition analysis, and metaphorical iconicity analysis. The conclusion is that the representation of Muslims in the four short stories ranges from perceiving Muslims as bed men living in hills and forest to perceiving Muslims as the slaves of the British. In all the representations, the British is not presented as an oppressor, instead as a benevolent master. It is a metaphor of Kiplingâs firm belief that the British were helping to civilize and educate a previously âsavageâ people. It disregards the fact that British colonization over India had ruined Islamic empire in India under Mogul Court sovereignty and ruined Indian economy and society organization.[Penelitian ini mengkaji empat cerita pendek Rudyard Kipling, âWee Willie Winkieâ, âThe Recrudescence of Imrayâ, âThe Story of Muhammad Dinâ, dan âWithout Benefit of Clergyâ. Adapun tujuan dari penelitian ini adalah mendeskripsikan representasi Muslim dalam empat cerita pendek tersebut dan mendeskripsikan bagaimana gambaran tersebut merepresentasikan kolonisasi Inggris atas India. Metode yang digunakan adalah metodologi kajian tekstual dengan analisis naratif, analisis oposisi-biner, dan analisis ikonositas metaforis. Kesimpulannya adalah bahwa representasi Muslim dalam empat cerita pendek tersebut merentang mulai dari muslim sebagai orang-orang jahat yang hidup di gunung dan hutan hingga sebagai budak orang Inggris. Dalam represestasi itu orang Inggris tidak pernah digambarkan sebagai penindas. Representasi ini merupakan metafora kepercayaan Rudyard Kipling bahwa kehadiran Inggris di India adalah untuk mengadabkan dan mendidik orang India yang semula liar. Representasi ini mengabaikan kenyataan bahwa kehadiran Inggris di India telah menghancurkan imperium Islam di India di bawah kedaulatan Istana Mogul dan meruntuhkan ekonomi dan susunan masyarakat India.]